Differences in palpebral fissure height depending on patient's intraoperative head position. (June 2019) - Nishioka, Hiroshi; Kondoh, Shoji; Yuzuriha, Shunsuke
Summary: Background: Blepharoptosis operations are performed under local anaesthesia, and it is necessary to determine the location where the levator aponeurosis is fixed to the tarsus by checking opening and closing of the eyelids during surgery. Changes in posture during the operation affect the facial condition in various ways. This study was performed to clarify the differences in palpebral fissure height according to intraoperative head position. Methods: Sixty subjects (48 women and 12 men aged 20–76 years) were enrolled in the study. The palpebral fissure height of the dominant eye was measured in the head-neutral position and 30° head-down position. Results: The total fissure height in the 30° head-down position was lower than that in the head-neutral position. Conclusions: The head-down position affects the patient's fissure height and may mislead the operator. Blepharoptosis operation under local anaesthesia should be performed with the patient in the head-neutral position.